1987
DOI: 10.1111/j.1445-2197.1987.tb01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Embolism: 1961–1985

Abstract: A review of arterial embolism to upper and lower limbs from 1961 to 1985. During this period 253 paticnts were treated for 269 episodes of embolus at the Princess Alexandra Hospital. The period was divided into S year intervals and analysis showed significantly increasing age for the population over this period. Similarly il decreasing mortality rate was noted during this period although limb salvage did not change after the initial S year period. There was a rising incidence of atherosclerotic ischaemic heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Whereas the incidence of rheumatic heart disease is decreasing, the incidences of atherosclerotic disease and arterial embolic disease are increasing. 2 The average age of patients with arterial embolic disease is 60-70 years, in accordance with our series, in which the average age was 58.7 years for men and 64.3 years for women.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Whereas the incidence of rheumatic heart disease is decreasing, the incidences of atherosclerotic disease and arterial embolic disease are increasing. 2 The average age of patients with arterial embolic disease is 60-70 years, in accordance with our series, in which the average age was 58.7 years for men and 64.3 years for women.…”
Section: Discussionsupporting
confidence: 85%
“…Englund and Magee reported that the average rates of mortality and amputation associated with arterial emboli were 15.6% and 8.2%, respectively. 2 Shifrin et al reported successful revascularization in 70.9% of limbs in which peripheral emboli had developed an average of 2.7 days before surgical intervention. 7 In our study, the amputation and mortality rates were 5.3% and 3.7%, respectively, increasing as the time between the development of the embolism and admission to hospital became longer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is significant difference between the development of emboly and arrival at hospital from the point of amputation rates. Englund and Magee reported the amputation rate due to acute arterial emboli as 8.2% [ 16 ]. Shifrin et al indicated that the successful revascularization rate was 70.9% for the patients admitted to hospital in 2–7 days [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it is understood from the study, late surgeries in acute arterial emboli increase the rate of amputations. It is reported in many studies that amputation rates were in the range of 0–18.9% [ 13 , 16 , 18 , 19 ]. The amputation rate in our study was found to be 13.6%.…”
Section: Discussionmentioning
confidence: 99%